Pengaruh Lama Penyimpanan Terhadap Kadar Vitamin C Buah Apel (Malus Sylvestris Mill) - Latief Abdul Maajid; Sunarmi Sunarmi; Ag. Kirwanto (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background: Vitamin C is easily soluble in water, and is the most labile vitamin because it is easily damaged by heat and storage. Vitamin C is contained in various fresh vegetables and fruits. One fruit that contains vitamin C is apple. The purpose of this study was to determine the effect of storage time on apple vitamin C levels. 12 apples were grouped into 4 groups at 0, 2, 4, and 6 days at room temperature. Vitamin C levels of apples were analyzed using a UV-Vis spectrophotometer at a wavelength of 290 nm. The highest vitamin C level was found in the 0 day storage period, which was equal to 0.335% and the lowest vitamin C level was found at 6 days of storage, which was 0.118%. Vitamin C levels of apples decrease with increasing storage time. Method: The data obtained were analyzed by one-way ANOVA test. Result:The results showed that storage time had a significant effect (p <0.05) on decreasing levels of apple vitamin C. Conclusion: Based on the results of these studies it can be concluded that the level of vitamin C in apples decreases along with the length of storage at room temperature. Therefore it is recommended that people consume fresh apples and not store apples at room temperature to get enough vitamin C.